An Analysis of Students’ Pronunciation Errors of English Dental Fricative at Universitas Dharmas Indonesia - sindi puji lestari; Martiya Nurni Khairita; Riyadi Saputra (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
This study aimed to identify the types of pronunciation errors and the factors causing errors in producing the English dental fricative sounds /θ/ and /ð/ among students of the English Education Study Program at Universitas Dharmas Indonesia. A descriptive qualitative research design was employed involving ten fourth-semester students as the participants. The data were collected through classroom observation, audio recordings, semi-structured interviews, and documentation. The collected data were analyzed using qualitative data analysis procedures consisting of data reduction, data display, and conclusion drawing. The findings revealed that substitution was the only type of pronunciation error identified. The voiceless dental fricative /θ/ was consistently substituted with /t/, while the voiced dental fricative /ð/ was substituted with /d/. No omission or distortion errors were found. The interview results indicated that the errors were influenced by first language interference, difficulties in tongue placement, limited pronunciation practice and exposure, preference for familiar sounds, and the tendency to prioritize fluency over pronunciation accuracy during conversation. The findings are expected to provide useful implications for English lecturers and students in improving pronunciation instruction, particularly in teaching English dental fricative sounds.